SOCIAL SUPPORT AND DIGNITY AS DETERMINANTS OF QUALITY OF LIFE IN PATIENTS WITH HEART DISEASE IN MEDAN CITY, INDONESIA - Pujiati, Lilis (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Heart disease remains a major global health burden and significantly affects patients’ quality of life. This study aims to examine the role of social support and dignity as determinants of health-related quality of life (HRQoL) among patients with heart disease in Medan City, Indonesia. A cross-sectional design was applied involving 271 respondents selected through structured sampling procedures. Data were collected using validated questionnaires measuring social support, dignity (dignity-related distress), and HRQoL. Descriptive statistics were used to characterize respondent characteristics, while bivariate analyses employed Gamma and Somers’d correlations to assess relationships among variables. Multivariate analysis was conducted using ordinal regression to identify dominant predictors of HRQoL. The results show that most respondents were male (51.3%), aged 55–64 years (27.7%), and married (83.0%). More than half of the participants reported high social support (56.1%) and good HRQoL (53.9%). Bivariate analysis indicated significant positive relationships between social support and HRQoL (p = 0.001) and between dignity and HRQoL (p < 0.001). Ordinal regression analysis revealed that both social support and dignity significantly influenced HRQoL simultaneously (p < 0.001), with a model explanatory power of 52.4% (Nagelkerke R² = 0.524). Social support emerged as the strongest predictor of HRQoL, compared with dignity. In conclusion, social support and dignity are significant determinants of HRQoL in patients with heart disease in Medan. Strengthening psychosocial support systems and maintaining patient dignity should be prioritized in cardiac care interventions to improve overall quality of life.